SatYajit Ray's The music room - Bandyopadhyay, Tarashankar 1898-1971 (The Criterion collection, 2011)
Evokes the crumbling opulence of the world of a fallen aristocrat desperately clinging to his way of life. His greatest joy is the music room in which he has hosted lavish concerts over the years, now a shadow of its former vivid self. An incandescent depiction of the clash between tradition and modernity, and a showcase for some of India's most popular musicians of the day